Las rutinas como estrategia de aprendizaje para desarrollar el pensamiento lógico matemático de los niños de 4 años de la I.E N°289 Hercilia Rojas Reategui - Portocarrero Rojas, Gaby (2010)
The titled investigation "The routines like learning strategy to develop the thought logical mathematician of the children of 4 years of age of the initial leve! in the Educational lnstitution N° 289 "Red Hercilia Reátegui", it arase because in this I.E. difficulties were observed in the mathematics's learning, insinuating the deficiency evidently in the teaching process - learning, with the consequent low learning in the children of 4 years of age of the initial level, considered for the present study. In this sense, and based on the investigations that preceded to the present, it was postulated that if those are applied "Routines" as learning strategy, then the children of 4 years of age of the initial leve! will improve significantly as for the development of their mathemati.cal logical thought, that which constituted the investigation hypothesis. To determine this influence, it was necessary to apply a pretest like diagnostic and a postest to verify the difference in the learnings achieved by the children. In the operative part, the investigation was driven under a design preexperimental with pre and post test, applied to a single group constituted by 20 children, which constituted the sample for the present investigation. As for the results, the hypothesis was contrasted by means of the test corresponding to the distribution t-Student, unilateral left, for the paired difference, settling down a level of trust for the experiment of 95%, with that which was possible to demonstrate that by means of the application of those Routines as learning strategy, the children were able to develop its mathematical logical thought, being evidenced in the improvements that you/they obtained in the seriación processes, classification, representation, space notion and number notion.